Examining the accumulated oxygen deficit method in breaststroke swimming - Reis, V. M.; Marinho, D. A.; Barbosa, F. P.; Reis, A. M.; Guidetti, L.; SIlva, A. J. (European Journal of Applied Physiology, 2010)
The present study investigated the accumulated oxygen deficit (AOD) method in breaststroke swimming with the aims to assess the reliability of the oxygen uptake/swimming velocity regression line and to quantify the precision of the AOD. Sixteen male swimmers performed two swimming tests in different days, with a 24-h recovery between tests: a graded swimming test and an all-out test. The all-out test was performed in one of two distances: 100 m (n = 7) or 200 m (n = 9). Through all testing, expired gases were collected breath by breath and analysed with a K4b2 Gas Analyser (Cosmed, Rome, Italy) connected to an AquaTrainer Valve (Cosmed, Rome, Italy). The standard error of the regression lines was ˜5-6 ml kg-1 min-1 and the regressions allowed an extrapolation of the energy cost to higher intensities with a standard error of the predicted value that was lower in the 200-m bout (˜3.5 ml kg-1 min-1) comparatively to the 100-m bout (˜6 ml kg-1 min-1). The AOD imprecision was calculated as the square root of the sum of the oxygen uptake measurement error and the standard error of the predicted value for energy cost. AOD imprecision was smaller in the 200-m bout (˜9 ml kg-1 min-1) comparatively to the 100-m bout (˜12 ml kg-1 min-1). However, since the AOD values during the two distances were small, the AOD relative errors can be viewed as high. Additionally, the data variability was considerable (95% confidence intervals of the linear extrapolation larger than 20 ml kg-1 min-1).